2010
DOI: 10.1038/jhg.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed resequencing analysis to identify rare variants in pooled DNA with barcode indexing using next-generation sequencer

Abstract: We have recently found that multiple rare variants of the glucocerebrosidase gene (GBA) confer a robust risk for Parkinson disease, supporting the 'common disease-multiple rare variants' hypothesis. To develop an efficient method of identifying rare variants in a large number of samples, we applied multiplexed resequencing using a next-generation sequencer to identification of rare variants of GBA. Sixteen sets of pooled DNAs from six pooled DNA samples were prepared. Each set of pooled DNAs was subjected to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…For example one cannot test for an association under different models, or look at gene-gene or gene-environment interactions. An alternative approach gaining popularity is the use indexed libraries [3], [23], [24] and combinational pooling strategies [25], [26]. Although at present there are limitations to the number of samples that can feasibly be pooled, taking into account the cost and time constraints of preparing a library for each sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example one cannot test for an association under different models, or look at gene-gene or gene-environment interactions. An alternative approach gaining popularity is the use indexed libraries [3], [23], [24] and combinational pooling strategies [25], [26]. Although at present there are limitations to the number of samples that can feasibly be pooled, taking into account the cost and time constraints of preparing a library for each sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is increasingly recognised that rare variants have a role in complex disease. An example in neurodegenerative disease is the glucocerebrosidase gene (GBA) in Parkinson's disease, individuals homozygous for mutations in this gene present with the Mendelian disorder Gaucher disease, while individuals heterozygous for the same mutations have an increased risk for Parkinson disease [3], [4] The cumulative frequency of GBA mutations in Parkinson disease cases can be as high as 9.0% compared to less than 0.5% in controls. Such variants are not included on commercial genotyping arrays but are only detected through re-sequencing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have suggested that the genetic variants for common diseases could have a wide spectrum of frequencies, ranging from rare to common, and that rare variants could exhibit a relatively large genetic effect (for example, odds ratio greater than 2). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] For example, in 2008, Stefansson et al 10 found that three rare deletions were associated with schizophrenia with the odds ratios of 2.7, 11.5 and 14.8, respectively. Some authors have proposed novel methods to detect associations with multiple rare variants for common diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed arrays will be just as informative as resequencing approaches would be where the information content of the dataset is limited by the frequency of recombination rather than by the detection of rare alleles. Furthermore, array-based analysis can be readily followed up by more targeted, sequencing-based approaches to identify rare alleles in genomic regions or germplasm accessions of interest (Mitsui et al 2010) With rapid changes in technology and computational resources, the two-step paradigm of SNP-discovery followed by SNP-detection is rapidly merging into a single, sequencebased process of simultaneous SNP discovery and detection (Craig et al 2008, Cronn et al 2008, Huang et al 2009. Once this becomes economically and logistically feasible for the rice community, direct sequencing will undoubtedly replace the use of fixed arrays.…”
Section: Advantages and Disadvantages Of Fixed Snp Assaysmentioning
confidence: 99%